IMPLEMENTATION OF CRM SYSTEM ON SALES OF COSMETIC SUPPLIES AND ACCESSORIES AT BERKAH JAYA KHALISA STORE - Putri Indriani; Nuriadi Manurung; Wan Mariatul Kifti (Universitas Serang Raya, 2025)
In today's digital era, the development of information technology is increasingly rapid and has a major impact on various sectors, including in the fields of business and trade. Customer Relationship Management (CRM) is a strategy used by companies to manage interactions with customers, with the aim of improving customer relationships, satisfaction, and loyalty. And for the problems that often occur in business owners of the Berkah Jaya Khalisa store, such as in the sales promotion section there is no, the store's income and expenditure reports are also not recorded. The transaction process used by the store still uses traditional methods, for example if there is a purchase of goods that are sold, the store owner must first record it on the invoice for the goods sold. The method used in this study is a qualitative method, namely a method that leads to in-depth understanding, by obtaining data through interviews and observations. The purpose of this study is to increase the efficiency of the sales process and expand the reach of the store's market through a system that can be accessed by customers from various regions, design a web-based CRM system that can facilitate the Berkah Jaya Khalisa Store in managing customer data and Assist sales through the website on the Berkah Jaya Khalisa store in increasing product sales turnover. And for the conclusions that can be drawn through the research that has been done, among others, such as the implementation of the CRM method at the Berkah Jaya Khalisa store, customers find it easier to find information about products and what items are available in the store. And customers can make orders online without having to come directly to the Berkah Jaya Khalisa Store.